The dead republic - Doyle, Roddy, 1958- (New York : Viking, 2010)
After being saved from death by none other than Henry Fonda and engaging in a brief but ill-fated collaboration with legendary director John Ford, Irish rebel Henry Smart ends up settling into a quiet life in a village north of Dublin, where he finds work as a caretaker for a boys' school and takes up with a widow O'Kelly (who may be his long-disappeared wife). But a political bombing in Dublin in 1974 puts him in the spotlight, and suddenly the secret of his rebel past is out.
Keywords: Young men -- Ireland -- Fiction; Revolutionaries -- Ireland -- Fiction; Ireland -- Fiction; Farce; Historical fiction